2016
DOI: 10.1515/tnsci-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Emotional conflict occurs at a late stage: evidence from the paired-picture paradigm

Abstract: The present study used paired-picture paradigm, where either congruent or incongruent emotional expressions were presented side by side to measure the neural correlates underlying the processing of emotional conflict effect. Event-related potentials were recorded while participants identified whether the valences of the paired-picture were consistent or not. The results showed that incongruent and congruent picture pairs both elicited larger N2 (210-310 ms) amplitudes than neutral pairs. In contrast, the confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…However, the majority of studies employed conflict paradigms (i.e., Simon or Flanker) in which conflict resolution is quite fast (as inferred from the response times) or focused on the influence of stimulus emotionality on conflict processing relative to nonemotional/emotionally neutral stimuli. Indeed, in emotional Stroop paradigms, it has commonly been found that conflict effects are reflected within later stages of neurophysiological processing (Pan, Lu, Chen, Wu, & Li, 2016;Shen, Xue, Wang, & Qiu, 2013). It therefore is possible that interference effects, as modulated by the emotional category, are not evident in the N2-ERP time window, because emotional conflict detection in Stroop tasks is dependent on the level of processing of the stimulus (MacLeod, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies employed conflict paradigms (i.e., Simon or Flanker) in which conflict resolution is quite fast (as inferred from the response times) or focused on the influence of stimulus emotionality on conflict processing relative to nonemotional/emotionally neutral stimuli. Indeed, in emotional Stroop paradigms, it has commonly been found that conflict effects are reflected within later stages of neurophysiological processing (Pan, Lu, Chen, Wu, & Li, 2016;Shen, Xue, Wang, & Qiu, 2013). It therefore is possible that interference effects, as modulated by the emotional category, are not evident in the N2-ERP time window, because emotional conflict detection in Stroop tasks is dependent on the level of processing of the stimulus (MacLeod, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Neither did we find interactive effects within the CSP data, which suggests that conflict monitoring or resolution processes in general are not modulated by varying the processing depth of emotional interfering stimuli. However, since results suggest that the CSP is mostly affected by pro-active control processes (Larson et al, 2014;Pan et al, 2016;Shen et al, 2013), this is an expected finding.…”
Section: Discussionmentioning
confidence: 71%
“…The ability to process relevant emotional information and ignore irrelevant emotional information is central for emotional self-regulation (Berg et al, 2016;Marusak, Martin, Etkin, & Thomason, 2015;Ochsner & Gross, 2005). These processes have extensively been examined using emotional interference (Stroop) tasks (Egner, Etkin, Gale, & Hirsch, 2008;Etkin, Egner, & Kalisch, 2011;Kunde & Mauer, 2008;McKenna & Sharma, 2004;Pan, Lu, Chen, Wu, & Li, 2016;Saunders, Milyavskaya, & Inzlicht, 2015;Schreiter, Chmielewski, & Beste, 2018b;Zinchenko, Kanske, Obermeier, Schröger, & Kotz, 2015). In the face-word Stroop task, for example, emotional faces are presented together with an emotional word that is either congruent or incongruent with the presented emotional face (Egner et al, 2008(Egner et al, , 2008Etkin et al, 2011;Kerns et al, 2004;Marusak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different stimuli have been used to induce mixed emotions in the laboratory, such as recalling naturally occurring situations [4, 5, 6], fictitious press advertisements [7, 8, 9, 10], listening to self-selected music [11], the paired-picture paradigm [12, 13, 14], or excerpts from motion pictures [15, 16, 17, 18]. However, these stimuli have been either ideographic (e.g., recall, self-selected music) or not naturalistic (e.g., scenes from motion pictures), less clear regarding simultaneity, stability, and time course of the mixed emotion (e.g., paired-picture paradigm), focused on a specific type of mixed emotion (e.g., nostalgia, poignancy), limited in number, or missing a neutral comparison condition.…”
Section: Paradigms For Generating Mixed Emotionsmentioning
confidence: 99%